THE IMPACT OF FREE FIRE ONLINE GAMES ON THE LEARNING MOTIVATION OF STUDENTS IN GRADE V SD 3 UNDAAN LOR - Halim Suryanto; Lintang Kironoratri; Lovika Ardana Riswari (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The Free Fire online game, which is very popular with students lately, has become a controversial thing in the realm of education. Because online games are considered to have a significant impact, both positive and negative. This is shown by data in the field found at SD 3 Undaan Lor, there are 4 grade V students who like to play Free Fire online games, from the activities of playing Free Fire online games that are carried out affect their learning motivation. The purpose of this study is to analyze the impact of Free Fire online games on students' learning motivation. This type of research is qualitative with a case study method. This research will be carried out at SD 3 Undaan Lor with the research subjects, namely 4 grade V students and grade V homeroom teachers. The results of the study found that students who play Free Fire online games have an impact on their learning motivation, the positive impact is to increase student learning motivation, increase students' concentration and focus in learning, interest in learning English and IPAS, and make new friends. Negative impacts cause decreased learning motivation, lazy learning, lack of focus, learning time imbalance, economic and student health disorders. Based on the results of the study, it can be concluded that the impact caused by playing Free Fire online games is in the form of positive and negative impacts. It is expected for students to understand and be able to sort out the impact caused by playing online games on learning motivation. The Free Fire online game, which is very popular with students lately, has become a controversial thing in the realm of education. Because online games are considered to have a significant impact, both positive and negative. This is shown by data in the field found at SD 3 Undaan Lor, there are 4 grade V students who like to play Free Fire online games, from the activities of playing Free Fire online games that are carried out affect their learning motivation. The purpose of this study is to analyze the impact of Free Fire online games on students' learning motivation. This type of research is qualitative with a case study method. This research will be carried out at SD 3 Undaan Lor with the research subjects, namely 4 grade V students and grade V homeroom teachers. The results of the study found that students who play Free Fire online games have an impact on their learning motivation, the positive impact is to increase student learning motivation, increase students' concentration and focus in learning, interest in learning English and IPAS, and make new friends. Negative impacts cause decreased learning motivation, lazy learning, lack of focus, learning time imbalance, economic and student health disorders. Based on the results of the study, it can be concluded that the impact caused by playing Free Fire online games is in the form of positive and negative impacts. It is expected for students to understand and be able to sort out the impact caused by playing online games on learning motivation.